The landscape of immunotherapy in metastatic urothelial carcinoma. Issue 6 (November 2019) - Teo, Min Yuen; Iyer, Gopa
Abstract : Purpose of review: This review provides an overview of clinical trials recently completed or currently ongoing evaluating the role of checkpoint blockade in metastatic urothelial carcinoma. Recent findings: In 2016, five immunotherapy agents were approved for metastatic urothelial carcinoma patients who had progressed on platinum-based chemotherapy All five agents evinced an approximately 20% overall response rate coupled with durability of response in a subset of these patients. Several putative predictive biomarkers of sensitivity to checkpoint blockade have been examined although which of these should be incorporated into standard practice is unclear. Moreover, as most patients do not respond to checkpoint blockade, research has focused on combination therapies in both the first-line and second-line settings. Summary: The durability of response and general tolerability of checkpoint blockade has transformed the treatment of metastatic urothelial carcinoma. However, only a minority of patients responds to single-agent therapy. Potential approaches to overcome this challenge include the incorporation of combination checkpoint blockade as well as chemotherapy and targeted agents.